Catecholase Activities of Copper(II) Complexes With N4 Ligands. (14th May 2021) - Sarkar, Shuranjan; Kim, Minyoung; Lee, Hong‐In
Abstract : Two new N4 ligands, 1, 2‐bis(2‐((pyridine‐2‐yl)methyleneamino) phenyl)ethane (L 1 ) and tris((2‐benzylideneamino) ethyl)amine (L 2 ), derived from 2, 2′‐ethylenedianiline and tren, respectively, were developed and their copper(II) complexes [Cu(L 1 )(ClO4 )](ClO4 )CH3 OH∙H2 O and [Cu(L 2 ) (CH3 COO)](ClO4 ) were synthesized. Crystal structures of the complexes were determined to show that both the complexes have distorted square pyramidal coordinations with very similar geometrical parameters. Catecholase activities of the complexes were investigated for the oxidation of 3, 5‐di‐ tert ‐butylcatechol (3, 5‐H2 dtbc) to 3, 5‐di‐ tert ‐butyl‐ o ‐quinone (3, 5‐dtbq) in the presence of O2 . Kinetic behaviors and spectroscopic measurements on the catalytic reactions were supportive to the proposal in which the mechanical pathway of the catecholase activities by the complexes were initiated by the anaerobic oxidation of 3, 5‐H2 dtbc to 3, 5‐dtbq, followed by the catalytic cycles with Cu(I) active forms. Abstract : Two new distorted square pyramidal Cu(II) complexes with N4 ligands were synthesized. Catecholase activities of the complexes were investigated on the oxidation of 3, 5‐H2 dtbc to 3, 5‐dtbq. Mechanistic pathway, in which the first step is an anaerobic oxidation of 3, 5‐H2 dtbc to 3, 5‐dtbq, followed by a catalytic cycle with Cu(I) active form, is suggested.